Improving outcomes in cerebral palsy with early intervention: new translational approaches - Anna Purna Basu (Frontiers Research Topics, 2015)
The aim of this Research Topic was to collate articles describing prediction of outcomes of pre- and perinatal lesions leading to cerebral palsy, basic research in animal models and human subjects, and ideas for, and trials of, interventions in the first two years of life.CP arises from insults to the sensorimotor cortex, subcortical axon tracts and subplate. The aetiology is complex and often multifactorial. The outcome is not simply a loss of voluntary control due to disruption of descending pathways, but also involves abnormal development of reflex and corticospinal circuitry. CP may be viewed as aberrant plasticity in response to a lesion, indeed, abnormalities in movement are subtle at first but develop subsequently. It is misleading to suppose that developmental mechanisms are self-reparative. The challenge is to understand activitydependent fine tuning of neural circuitry during normal development and to find how to promote desirable plasticity whilst limiting undesirable effects following developmental lesions. However, before proposing interventions, we have to develop our ability to predict the severity of neonatal insults.We solicited a variety of articles, including long and short reviews, original research and opinion pieces, from both basic scientists and clinicians. Likewise we, as editors, have complementary knowledge and experience in this area. Anna Basu is an academic pediatric neurologist and Gavin Clowry is a developmental neuroscientist.